(:unas) unassigned - Chrysostomou, Christis (My University, 2019)
The purpose of these committees was the visit to Private Tertiary Engineering Schools in Cyprus who have requested to be accredited and to investigate whether the Schools satisfied the criteria specified in the Law for Private Tertiary Schools. The committees were submitting a report to the General Director of the Ministry of Education, which was used as the basis for the accreditation or not of the program.